Development of Interactive Media-Based Teaching Materials to Improve Conceptual Understanding of Measurement for Students at Makassar Maritime Polytechnic - Gradina Nur Fauziah; Agustina Setyaningsih; Annisa Rahmah; Napsawati Napsawati (PT Publikasiku Academic Solution, 2025)
This research aims to develop and evaluate interactive media-based teaching materials to enhance conceptual understanding of measurement among students at Makassar Maritime Polytechnic. Conventional teaching methods, relying on textbooks and lectures, have proven ineffective in fostering the visual and spatial intuition necessary for maritime applications. Employing a modified 4D development model (Define, Design, Develop), the research created teaching materials using Flipbook PDF Professional, integrating text, images, videos, animations, and interactive quizzes in HTML5 format. Validation by experts yielded high scores: material validity at 91.11% and media validity at 95.45%, both categorized as